2013
DOI: 10.1007/s11764-013-0294-6
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and efficacy of a supervised exercise intervention in de-conditioned cancer survivors during the early survivorship phase: the PEACH trial

Abstract: Exercise interventions commenced in the early survivorship phase appear safe, feasible and may lead to improvements in QOL and fatigue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 47 publications
2
31
0
Order By: Relevance
“…Of the sixteen studies involving patients in active treatment [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] , six demonstrated that, compared with the control group, the intervention group experienced significant improvements in qol 30,31,33,[38][39][40]43 . In the thirteen post-treatment intervention studies 10,12,14,[45][46][47][48][49][50][51][52][53][54] , two reported similar significant differences between groups 46,49 .…”
Section: Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…Of the sixteen studies involving patients in active treatment [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] , six demonstrated that, compared with the control group, the intervention group experienced significant improvements in qol 30,31,33,[38][39][40]43 . In the thirteen post-treatment intervention studies 10,12,14,[45][46][47][48][49][50][51][52][53][54] , two reported similar significant differences between groups 46,49 .…”
Section: Quality Of Lifementioning
confidence: 99%
“…Of the sixteen rcts that measured muscular or aerobic fitness, or both 10,14,29,30,34,35,37,39,40,[44][45][46][47][48]52,54 , eleven found significant positive changes in the exercise groups 10,14,29,30,34,35,37,39,[44][45][46]48 . A systematic review found substantial increases in muscular strength and endurance with resistance training for patients on androgen deprivation therapy 21 .…”
Section: Muscular and Aerobic Fitnessmentioning
confidence: 99%
“…Of the sixteen rcts involving patients in active treatment [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] , seven reported significant differences between the intervention and control groups (Table vi) 23,24,26,[31][32][33]36 . In the thirteen posttreatment intervention studies [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] , two reported significant qol improvement in the exercise groups 41,42 . In particular, patients with lymphedema experienced qol benefits, and aerobic and resistance exercises were both safe for women who had undergone breast and axillary surgery 6,7,38,39,44 .…”
Section: Qol and Muscular And Aerobic Fitnessmentioning
confidence: 99%
“…Of the sixteen rcts that measured muscular or aerobic fitness or both 22,23,27,28,30,32,33,37,38,40,41,[43][44][45][46][47] , twelve found significant positive changes in the exercise groups (Table vi) 22,23,27,28,30,32,37,38,41,43,44,46 . One systematic review 14 found substantial increases in muscular strength and endurance with resistance training for patients on androgen deprivation therapy (Table v).…”
Section: Qol and Muscular And Aerobic Fitnessmentioning
confidence: 99%
See 1 more Smart Citation